Percepción de los estudiantes de la carrera de Comunicación de la UTMACH, sobre el debate presidencial de la segunda vuelta del proceso electoral 2025 - Vivanco Caamaño, Mayerlin Alejandra (Machala : Universidad Técnica de Machala, 2025)
This research analyzes the perception of communication students on the presidential debate of the second round, considering the influence of traditional media and content generated in social networks, and aims to analyze the perception of students of the communication career of the Faculty of Social Sciences of the Technical University of Machala on the presidential debate of the second round of the electoral process 2025. The methodology of this research has a mixed approach that has as data collection techniques a structured survey directed to 132 students and a semi-structured interview directed to two experts in political communication. The study allowed identifying the preferred channels of information access, showing that digital platforms, especially TikTok and X had greater emotional and discursive impact than television. The results show a critical perception regarding the candidates' performance, the clarity of their proposals and the relevance of the debate format, highlighting that emotional language and gestures had more influence than rational arguments in the students' assessment. The interviews confirmed the absence of local issues in the discourse and evidenced the primacy of symbolic narratives. It is concluded that youth political consumption is mediated by emotionality, the digital environment and information fragmentation.
La presente investigación analiza la percepción de los estudiantes de Comunicación en la sobre el debate presidencial de segunda vuelta, considerando la influencia de los medios tradicionales y los contenidos generados en redes sociales, y tiene como objetivo analizar la percepción de los estudiantes de la carrera de Comunicación de la facultad de Ciencias Sociales de la Universidad Técnica de Machala sobre el debate presidencial de segunda vuelta del proceso electoral 2025. La metodología de esta investigación tiene un enfoque mixto que tiene como técnicas de recolección de información una encuesta estructurada dirigida a 132 estudiantes y una entrevista semi estructurada dirigida a dos expertos en Comunicación Política. El estudio permitió identificar los canales preferidos de acceso informativo, evidenciando que las plataformas digitales, especialmente TikTok y X tuvieron mayor impacto emocional y discursivo que la televisión. Los resultados muestran una percepción crítica respecto al desempeño de los candidatos, la claridad de sus propuestas y la pertinencia del formato del debate, destacando que lenguaje emocional y los gestos influyeron más que los argumentos racionales en la valoración estudiantil. Las entrevistas confirmaron la ausencia de problemáticas locales en el discurso y evidenciaron la primacía de narrativas simbólicas. Se concluye que el consumo político juvenil está mediado por la emocionalidad, el entorno digital y la fragmentación informativa.
Keywords: MEDIOS DIGITALES; DEBATE; SEGUNDA VUELTA; UNIVERSITARIOS